Analisis Pengaruh Dana Pihak Ketiga, Pembiayaan, Bancassurance Terhadap Laba Dan Dampaknya Pada Kesejahteraan Masyarakat (Studi Kasus Bank Syariah Di Indonesia) - Dian Adila Putra; Marliyah Marliyah; Muhammad Yafiz (Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to determine how the direct influence of deposits, financing and bancassurance on the profits of Islamic banks and the welfare of society and indirect influence or through the intervening variables of profits on the welfare of society and total influence. This type of research is quantitative research. Data collection methods used are documentation methods based on data in the form of monthly financial statements for the period 2014-2018 and per capita income data that has been published. The method of data analysis in this study is by using the path analysis method. The results of the study show that financing significantly affects earnings while third party funds and bancassurance do not directly affect earnings. Deposits and profits of Islamic banks significantly influence directly on public welfare and bancassurance negatively influences people's welfare while financing does not. Financing indirectly significantly influences welfare through profit variables, whereas DPK and bancassurance do not. Business activities of Islamic banks have a role in addition to achieving company profits, also have a positive impact on the welfare of the Indonesian people. Funding and third party funds that generate profits are a determining factor for improving community welfare rather than bancassurance sales.